Study of defect formation mechanisms in Li2ZrO3/MgLi2ZrO4 ceramics using EPR spectroscopy - Dmitriy I. Shlimas; Ainagul A. Khametova; Artem L. Kozlovskiy; Maxim V. Zdorovets (Optical Materials: X)
The article presents the results of experimental studies of the effect of the stabilizing MgO dopant using the electron spin resonance (ESP) method on enhancement of the stability of Li2ZrO3 ceramics to defect formation processes and accumulation of radiolysis products in the near-surface layer in the case of high-dose irradiation with protons simulating the hydrogenation effects characteristic of processes associated with tritium production. During the conducted studies, it was established that the addition of the stabilizing MgO dopant results in formation of inclusions in the form of the tetragonal MgLi2ZrO4 phase, which leads to an increase in the resistance of the near-surface layers to destructive damage due to the accumulation of structural damage (oxygen vacancies and point defects), as well as products of the physicochemical processes of radiolysis, characteristic of high irradiation fluence values. It was found that in the case of unmodified Li2ZrO3 ceramics, the formation of HC2 – centers is observed at a fluence of 1016 proton/cm2, while for two-phase ceramics, the formation of HC2 – centers is observed at higher fluences, while the intensity of the bands is significantly less than in the case of single-phase unmodified ceramics. The difference in the nature of changes in the intensities of singlet bands responsible for the presence of vacancy defects in the damaged layer, as well as HC2 – centers for single-phase and two-phase ceramics is a direct confirmation of the inhibition of structural degradation mechanisms in two-phase ceramics.